Perancangan Sistem Absensi Berbasis Mobile Untuk Meningkatkan Efisiensi Pencatatan dan Pemantauan Kehadiran Pegawai di Playlicious - Muhammad Aziz Zen; Farizi Ilham; Nila Prawitasari; Mohammad Ilham Alfalal AL fikri (GLOBAL SCIENTS PUBLISHER, 2026)
The employee attendance recording process in the company was previously conducted manually, causing delays, data inaccuracies, and difficulties in monitoring attendance. To address these issues, a mobile-based attendance system was designed to improve efficiency, accuracy, and accessibility for both employees and management. The system was developed using web and Android platforms, with observation, interviews, literature study, and descriptive methods applied for requirements analysis and system design. Key features include employee login, real-time attendance recording, admin monitoring, and monthly attendance reports. Testing showed that the system accelerates the attendance process, reduces recording errors, and facilitates employee attendance monitoring. With the implementation of this system, the company can manage attendance data in a structured, transparent, and integrated manner, thereby enhancing human resource management quality.